EVALUASI PENERAPAN APLIKASI SICantik DALAM PENGELOLAAN DATA PERIZINAN (APDP) BERBASI IT: (Studi Mall Pelayanan Publik Kabupaten Gresik) - Sucahyo, Imam; Rahmadi, Andhi Nur; Mardianto, Agus (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Bhayangkara Surabaya, 2025)
The use of information technology transforms government activities with the aim of increasing the effectiveness and efficiency of government administration which has an impact on the quality of service. One of the innovations from the Ministry of Communication is SiCantik Cloud, a smart application for integrated public cloud-based licensing services that can be used by government agencies independently. The Gresik Regency Investment and Integrated One-Stop Service Office (DPMPTSP) is currently implementing the SiCantik Cloud application in licensing services. This study aims to evaluate the implementation of the SiCantik Cloud application based on the Regulation of the Minister of State Apparatus Empowerment and Bureaucratic Reform Number 15 of 2014. The determination of informants using the purposive sampling method totaling 6 informants consisting of DPMPTSP employees) Gresik Regency and the community as users of the SiCantik application. Based on data from findings in the field, the implementation of the SiCantik Cloud application in Gresik Regency has been able to provide a positive impact on services that can increase the issuance of business permit documents every year. The features in the Sicantik application are considered simple and easy enough for the public to understand, although there are still people who do not fully understand how to operate the Sicantik application. The results of the evaluation by researchers based on the indicators of Requirements, Systems, mechanisms and procedures, Service period, Costs, Service products, and Complaint handling are considered to be in accordance with the SOP stated in the Gresik Regent Regulation Number 94 of 2021 concerning the Implementation of Business Licensing and Non-Licensing Services in Gresik Regency and are very helpful in terms of services that are easy and fast. Keywords: SiCantik Application, Evaluation, Public Service.